2019
DOI: 10.1088/1755-1315/309/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Air-Drying on Yield of Essential Oil from Sereh Wangi Plants Cultivated on Degraded Land

Abstract: Citronella (Cymbopogon nardus L) is a kind of plant producing essential oil. The cultivation does not require special requirements, can be grown on less fertile soil, and able to rehabilitate degraded and critical lands. In this study, 5 levels of drying duration (0, 1, 2, 3, and 4 days) were observed for their effect on the yield of citronella oil grown at 3 critical levels of land (quite critical, critical, and very critical). The experiment was designed in a completely randomized block design with 3 replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Numerous studies have confirmed that EO yield decreases with time [24][25][26] or at least reaches equilibrium at some point without further increase [27][28][29]. There are also data from the literature suggesting different effects of drying on EO content [30], as some studies noted a significant decrease in yield [31], while others reported an increase [26]. These differences could be due to the drying time as well as the temperature used [30].…”
Section: Eo Extractionmentioning
confidence: 99%
“…Numerous studies have confirmed that EO yield decreases with time [24][25][26] or at least reaches equilibrium at some point without further increase [27][28][29]. There are also data from the literature suggesting different effects of drying on EO content [30], as some studies noted a significant decrease in yield [31], while others reported an increase [26]. These differences could be due to the drying time as well as the temperature used [30].…”
Section: Eo Extractionmentioning
confidence: 99%
“…Rendemen Varietas Sitrona 2 Agribun dari hasil penelitian lebih tinggi (P4 =1,95) dibandingkan dari penelitian Kementerian Pertanian (2016) sebesar 1,83% yang dilakukan di kebun percobaan monokultur. Penelitian (Zheljazkov et al 2011) yang dilakukan di Verona dan Poplarville, Mississippi dengan perlakuan pemupukan menghasilkan rendemen 0,33% -0,55%, sedangkan penelitian Achmad et al (2019) di Sungai Gelam, Muaro Jambi dengan perlakuan berbagai cara distilasi menghasilkan rendemen sebesar 0,66%-0,68%. Hasil ini membuktikan bahwa Varietas G2 dan Sitrona 2 Agribun mampu menghasilkan rendemen yang tinggi.…”
Section: Pembahasanunclassified
“…Indonesian citronella oil in the world market is known as Citronella Oil of Java [2]. Citronella can be an alternative that can be used for development on dry land and sub-optimal land [3][4][5]. The nature of its ease of being able and easy to grow in various conditions is characterized by its special morphological characters such as long fibrous roots and clumps that are easy to grow such as weeds, long and pointed leaves that require relatively less water and are able to adapt in several conditions so that this plant has economic value prospect that deserve to be taken into account [6,7].…”
Section: Introductionmentioning
confidence: 99%